Temporary exports and characteristics of destination countries: First evidence from German transaction data - Joachim Wagner (Kiel Institute for the World Economy (IfW), 2018)
This paper uses information on all export transactions of goods by German firms with countries outside the European Union from 2009 to 2014 to document for the first time the patterns of export participation at the firm-good-destination level over time and to investigate the link between the duration of export patterns and characteristics of destination countries. It turns out that only some seven percent of all combinations were recorded in each year while more than half of all patterns are only observed once. In line with theoretical hypotheses the likelihood of permanent trade patterns increases within a firm with proximity and market size of destination countries.
Keywords: F14; 330; temporary exports; permanent exports; transaction level data; Germany